Imperfections in the Legislation Governing the Criteria for Awarding Public Contracts and Their Impact on the Water Sector in the Implementation of Projects Financed by The EU Cohesion Fund - Neychev, Stoyan (Research Papers, 2023)
The subject of the study is an analysis of some provisions of the current legislation in the field of public procurement with a focus on the criteria for their award. As a result, some weaknesses in the national legislation have been identified, which are an obstacle to the implementation of measures financed through the Cohesion Fund (CF) of the European Union (EU) in the “Water” sector. The conclusions established during a comparative analysis against the applicable secondary law of the Union can serve as proposals for legislative amendments, since the identified imperfections have a negative impact not only on the sector, but also on the whole in the management of public resources in conditions of limitations on their size.In a practical aspect, the research aims (and the end result) to make a connection between gaps in the national regulatory framework regarding the awarding of contracts for public procurement and their influence regarding the state of operators in the “Water” sector, and in – broad aspect – the permanent impossibility of achieving compliance with EU law in the sector caused by them.Regarding the research methodology, methods such as analysis and synthesis, induction and deduction, comparative analysis and comparison, and in cases where it is possible and applicable – empirical verification have been applied. In addition, processing of data acquired in the course of the research is applied (case law available).
Keywords: Public procurement criteria; Water sector